2012
DOI: 10.2174/1874325001206010305
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Navigation in High Tibial Osteotomy: A Systematic Review of the Literature

Abstract: High tibial osteotomy (HTO) is a procedure which aims to change the mechanical axis of the lower limb, transferring the body weight across healthy articular cartilage. Several studies have shown that accurate correction is the leading predictor for success.In this article, we systematically review the computer-assisted techniques that have been used in attempts to increase the accuracy of the surgery and improve postoperative outcomes. The results of the cadaveric and clinical studies to date are presented and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…In a recent systematic review about the navigation technique, Picardo et al [24] found only two studies comparing the conventional and the navigation techniques, evaluating the mechanical axes, tibial slope and the clinical results, both very similar to our study. The mechanical axis was better controlled, but the tibial slope and the clinical evaluation were different.…”
Section: Discussionsupporting
confidence: 87%
“…In a recent systematic review about the navigation technique, Picardo et al [24] found only two studies comparing the conventional and the navigation techniques, evaluating the mechanical axes, tibial slope and the clinical results, both very similar to our study. The mechanical axis was better controlled, but the tibial slope and the clinical evaluation were different.…”
Section: Discussionsupporting
confidence: 87%
“…There are also technique-related disadvantages, such as the long learning curve, line of sight issues, registration failures, and mechanical or software malfunctions 1). Gebhard et al16) reported on the influence of surgeon's experience and perioperative complications in computer-assisted open-wedge HTO.…”
Section: Disadvantages and Literature Reviewmentioning
confidence: 99%
“…High tibial osteotomy (HTO) is a procedure that realigns the weight-bearing line from the affected medial compartment to the relatively unaffected lateral compartment of the knee 1). Interest in HTO as an adjunctive procedure has increased recently due to technical advances in cartilage healing procedures and meniscal transplantation for which malalignment would otherwise represent a contraindication.…”
mentioning
confidence: 99%
“…The most common procedure in use is high tibial osteotomy (HTO) and was introduced in 1958. 30,31 Due to the common presentation of varus malalignment in young, active patients with medial osteoarthritis the osteotomy is typically conducted as a medial opening wedge osteotomy. Multiple fixation techniques are established.…”
Section: Navigation In Osteotomymentioning
confidence: 99%